Ecuador : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2006)
This Selected Issues paper analyzes economic performance of Ecuador under dollarization. The paper reviews the principal trade-offs normally associated with official dollarization, and their specific relevance to Ecuador. It discusses Ecuador's performance under the dollarization regime, highlighting the country's main achievements and challenges in the macroeconomic and structural areas. The paper draws some conclusions and discusses what dollarization implies for Ecuador's reform agenda in the future. The paper also assesses sustainability of Ecuador's fiscal policy and explores criteria that could guide the setting of fiscal policy in the future.